DIRECTIONS OF STRATEGIC DEVELOPMENT OF "GREEN" ENERGY IN THE WORLD - FEDORCHUK, Volodymyr; FEOFANOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines directions of strategic development of "green" energy in the world. Summarizing the approaches to defining the concepts of green, clean and renewable energy sources existing in the scientific literature, the authors conclude that renewable energy is obtained from sources that are constantly renewed and subject to processing. Research results prove that in recent years, national policies, strategies and plans for the development of renewable energy are increasingly oriented towards sustainable development.The renewable energy market, which was estimated at $881.7 billion in 2020, is expected to reach $1,977.6 billion between 2023 and 2030. USA. According to market research, the demand for clean energy alternatives is growing at an exponential rate, and supportive government policies are essential to facilitate the transition.Some of the actual problems associated with renewable green energy systems come from their specific source, referring to the nature of the source, which can be intermittent, highly dependent on weather conditions or the type of technology used, storage capacity, training support, necessary where there is no service system.A review of existing research shows that solar energy is used globally and is becoming more common as a means of water desalination, home heating and electricity generation, and the cost of producing solar panels has fallen significantly over the last decade. In this context of energy needs, solar panels have become a sustainable and most cost-effective source of electricity.The use of hydropower is occurring on a large scale around the world, contributing to the achievement of Sustainable Development Goals 7 (SDG7).Thus, the main directions of the strategic development of "green" energy are the development of energy generation from renewable green sources with zero or minimal impact on the environment, such as the sun, wind, hydroelectric power, geothermal energy, tidal and ocean energy, biomass and biofuel. The cheapest and most environmentally friendly source of energy is renewable energy, since it can be produced domestically, which minimizes the demand for energy imports. In recent years, renewable green energy has continued its downward trend due to supply chain difficulties, while rising fossil energy prices have yet to fully show their impact on the cost of green energy projects.
Keywords: energy; green energy; global market; sustainable development